Misuse of Facebook user data - Hernández , Leonel; Juniarti Fatimah, Tri; Fautngilyanan, Petrus Jack; Hamid, Sayed Rahman; Pramudhita, Setya Rahadi; Simbolon, Triyanti (Bulletin of Social Informatics Theory and Application, 2021)
Nowadays, we live when technological developments have developed rapidly, especially in the communications and information sector. One of the triggers is social media, including Facebook. In 2010, there were around 24 million Facebook users in Indonesia. In building social relationships, of course, personal information is needed from someone. The same is the case when using social media. When you want to create a Facebook account, users will be asked to provide various personal data. This functions so that users can recognize one another. Besides that, it can also help Facebook in securing user accounts. But by sharing personal data will undoubtedly pose a risk of being misused. Apart from data leaks due to Facebook's shortcomings, this is also inseparable from users' negligence in safeguarding their data. This research explores the unawareness of Facebook users in protecting their data. This research will show the consequences of a lack of attention in maintaining personal data and show how to protect personal data to increase the awareness of Facebook users in safeguarding their data.